Results from a soil improvement and fertilizing test on fen land at Leteensuo - Yrjö Pessi (Agricultural and Food Science, 1961)
Clay and sand, used as soil improving agents, have increased the hay crops as well as the cereal crops. When the fertilization contained phosphates only, the increases in crop yield produced by the soil improvement were quite high. In this case clay developed a higher effect than sand. In connection with phosphate plus potassium fertilization both kinds of mineral soil were approximately equal in value, but their effect fell considerably below that of phosphate fertilization alone. These agents have thus a remarkable potassium fertilizing effect. However, potassium fertilization was not able to account for the entire crop yield-increasing effect of mineral soil. The highest increases in crop yield per unit of mineral soil addition were obtained with the mineral soil quantity of 100 m3 per hectare. The addition of mineral soil has a prolonged effect since the effect has not decreased in the 30 years since the latest soil improving treatment in this test. Phosphate and potassium fertilization are both necessary. For spring cereals and for the annual top dress fertilization of hay meadows the superphosphate quantity of 200—300 kg per hectare is adequate. The requirement of potassium fertilizer varies according to the quantity of soil improving agents and their quality. In all circumstances 200 kg 50 % potassium salt per hectare seems to be a sufficient potassium fertilization for the plants considered in this test. A slightly higher quantity is thought to be necessary for the top dress fertilization of hay meadows without soil improving agents.